2, 6-Diamino-1-N-methylpyrimidine as new fluorescent probe for palladium(II) determination using hyphenated technique. Issue 7 (September 2017) - Volovenko, Olesya; Keda, Tetiana; Skreminska, Natalia; Milokhov, Demyd; Khilya, Olga; Zaporozhets, Olga
The selective and sensitive hyphenated technique for Pd(II) fluorescence and spectrophotometric determination was proposed. The procedure was based on preliminary solid-phase extraction of [PdCl4 ] 2− onto silica modified with quaternary ammonium salts, with the subsequent elution from the surface by 2, 6-diamino-1- N -methylpyrimidine solution and measurement of the fluorescence intensity. The luminescence enhancement effect of 2, 6-diamino-1- N -methylpyrimidine in the presence of Pd(II) due to the complex formation was applied to the development of sorption-spectroscopic techniques for detecting trace amounts of palladium in solution.